Pengaruh Praktik-Praktik Supply Chain Management terhadap Kinerja Perusahaan pada Industri Furnitur di Palangka Raya - Hestina Pratiwi; Yohanes Kalvin Anggen; Deddy Rakhmad Hidayat (Program Pascasarjana Universitas Palangka Raya dan (and) Ikatan Ahli Teknik Penyehatan dan Teknik Lingkungan IndonesiaÂ (IATPI), 2020)
This research purpose is to analyze the impact of supply chain management practices on firm performance in furniture industry of Palangka Raya. Research method deskriptif quantitative, the number of respondents was 60 people. the number of samples collected was 46 respondents. The sampling technique use judgment sampling, with criteria for the leadership of furniture industry in Palangka Raya Data collection techniques using a questionnaire with a likert scale, Data analysis techniques used descriptive statistical analysis and multiple linear regression. The analysis shows that the results of strategic supplier partnership, customer relationship, level of information sharing, quality of information sharing, postponement the partially have a significant impact on firm performance. the simultaneously supply chain management practices have a significant impact on firm performance.